Pragmatic randomised controlled trials in parenting research: the issue of intention to treat. Issue 10 (13th September 2006) - Whittaker, Karen; Sutton, Chris; Burton, Chris
Abstract : Study objective: To evaluate trials of parenting programmes, regarding their use of intention to treat (ITT). Design: Individual trials included in two relevant Cochrane systematic reviews were scrutinised by two independent reviewers. Data on country of origin, target audience, trial type, treatment violations, use of ITT, and the management of missing data were extracted. Main results: Thirty trial reports were reviewed. Three reported the use of an ITT approach to data analysis. Nineteen reported losing subjects to follow up although the implications of this were rarely considered. Insufficient detail in reports meant it was difficult to identify study drop outs, the nature of treatment violations, and those failing to provide outcome assessments. In two trials, study drop outs were considered as additional control groups, violating the basic principle of ITT. Conclusions: It is recommended that future trial reports adhere to CONSORT guidelines. In particular ITT should be used for the main analyses, with strategies for managing treatment violations and handling missing data being reported a priori. Those conducting trials need to acknowledge the social nature of these programmes can sometimes result in erratic parent attendance and participation, which would only increase the chances of missing data. The use of approaches that can limit the proportion of missing data is therefore recommended.